The Utilization of Digital-Based Chain Picture Game Using Gartic Phone Application to Improve Students' Mastery of Arabic Vocabulary - Nadhif, Muhammad Fahrun; Annis Berliani Premaswari (ATHLA : Journal of Arabic Teaching, Linguistic and Literature, 2023)
Digital-Based Chain Picture Game using the Gartic Phone application to improve students' mastery of Arabic vocabulary. The research employed a Quasi-Experimental Design with a Nonequivalent Control Group Design. The participants consisted of students from Grade VIII at MTs N 1 Klaten. The experimental group utilized the Digital-Based Chain Picture Game with the Gartic Phone application as the intervention, comprising 30 participants. Meanwhile, the control group did not receive any intervention and consisted of an equal number of 30 students. Data on the mastery of Arabic vocabulary were collected before and after the intervention using a vocabulary test. Additionally, students' perceptions regarding their experience using the Digital-Based Chain Picture Game with the Gartic Phone application were collected through a questionnaire employing the Technology Acceptance Model (TAM) instrument. Data analysis was conducted using appropriate statistical methods to compare the differences in vocabulary mastery between the experimental and control groups. The findings of this study are expected to provide a better understanding of the effectiveness of using the Digital-Based Chain Picture Game with the Gartic Phone application in enhancing students' mastery of Arabic vocabulary. It also serves as a recommendation for Arabic language instructors to incorporate the Gartic Phone application as one of the media to improve Arabic vocabulary mastery.